Approach to the diagnosis of neurotransmitter diseases exemplified by the differential diagnosis of childhood-onset dystonia - Assmann, Birgit; Surtees, Robert; Hoffmann, Georg F. (Annals of neurology, 2003)
We present our approach to the diagnosis of pediatric neurotransmitter diseases exemplified by the differential diagnosis of children presenting with dystonia. This approach is based upon the primary aim of early diagnosis of treatable conditions and the need for a logical series of investigations. We have tried to be comprehensive with our coverage but are aware that “new” pediatric neurotransmitter diseases continue to be delineated and that, similarly, a proportion of children presenting with dystonia remain undiagnosed. If this is the case, all of the investigations suggested here may need to be performed regardless of age and presentation. However, of more value is a careful clinical reevaluation. Ann Neurol 2003;54 (suppl 6):S18-S24
Gesehen am 22.12.2020